The Effect of Sugar and Agar-agar Concentration on Nypa Fruit Slice Jam - Surhaini, Surhaini; Mursyid, Mursyid (Indonesian Food Science and Technology Journal, 2017)
Nypa fruticans or known as nypa produces considerable amount of fruit with high content of carbohydrate. The mesocarp of the mature fruit is a potential source of energy but underutilised. This research was conducted to study the production of nypa slice jam by focussing on the effect of sugar and agar-agar concentration on the physical, chemical and sensory properties of nypa slice jam. Sugar and agar-agar concentration affect rendemen, crude fibre content, total soluble solid, water content, colour, texture, taste, flavour and overal acceptance of slice jam from nypa fruit.